Protein adduct binding properties of tabun-subtype nerve agents after exposure in vitro and in vivo. (15th March 2020) - Fu, Feiyan; Liu, Haibo; Gao, Runli; Zhao, Pengcheng; Lu, Xiaogang; Zhang, Ruihua; Wang, Liangliang; Wang, Hongmei; Pei, Chengxin
Highlights: The binding properties of tabun-subtype nerve agents were investigated. The binding mechanism with selectivity to lysine residues were studied. K525 and K414 can serve as the primary biomarkers for traceability of GAs exposure in humans. Abstract: Upon entering the body, nerve agents can bind active amino acid residues to form phosphonylated adducts. Tabun derivatives ( O -alkyl- N, N- dialkyl phosphoroamidocyanidates) have strikingly different structural features from other G-series nerve agents, such as sarin and soman. Here, we investigate the binding mechanism for the phosphonylated adducts of nerve agents of tabun derivatives. Binding sites for three tabun derivatives, O -ethyl- N, N - dimethyl phosphoramidocyanidate (GA), O -ethyl- N, N -ethyl(methyl) phosphoramidocyanidate, and O -ethyl- N, N -diethylphosphoramidocyanidate were studied. Quadrupole-orbitrap mass spectrometry (Q-Orbitrap-MS) coupled to proteomics was used to screen adducts between tabun derivatives and albumin, immunoglobulin, and hemoglobin. The results reveal that all three tabun derivatives exhibit robust selectivity to lysine residues, rather than other amino acid residue types. A set of 10 lysine residues on human serum albumin are labeled by tabun derivatives in vitro, with K525 (K*QTALVELVK) and K199 (LK*CASLQK) peptides displaying the most reactivity. Tabun derivatives formed stable adducts on K525 and K414 (K*VPQVSTPTLVEVSR) for at least 7 days and on K351 (LAK*TYETTLEK) for at least 5 days in a rabbit model. Three of these peptides—K525, K414, and K351—have the highest homology with human serum albumin of all 5 lysine residues that bound to examined rabbit blood proteins in vivo . Molecular simulation of the tabun-albumin interaction using structural analysis and molecular docking provided theoretical evidence supporting lysine residue reactivity to phosphonylation by tabun derivatives. K525 has the lowest free binding energy and the strongest hydrogen bonding to human albumin. In summary, these findings identify unique binding properties for tabun derivatives to blood proteins.